From Bare to Birch: Large-Scale Ecosystem Restoration in Iceland - Orradottir, B. (Berglind); C. Barrio, I. (Isabel); Boyaninska, D. (Daniela) (2019)
The case of Hekluskógar (meaning “Hekla woodlands”) in South Iceland examines how to transition from barren desertified land to a resilient and healthy woodland that can provide ecosystem services to the people in the area and beyond. The case provides a thorough description and background of the many components involved in the largest reforestation project in Europe as of 2018. The area surrounding Mount Hekla, one of Iceland’s most active volcanos, has suffered a steady deterioration. The area was once covered in birch woodlands with fertile soils, but it is nowadays mostly bare. Human activity including deforestation and overgrazing has largely contributed to the degradation of the ecosystems, although the destruction is also interlinked to the volcanic eruptions and the cooling climate in the Middle Ages. Following the degradation of vegetation, wind and water easily transported the loose soil, causing further erosion and uprooting vegetation. The lack of vegetation will make the effects of future eruptions more catastrophic to the land and community if the ecosystem is not restored. Native birch is able to restrain the movement of volcanic ash and is adapted to the harsh weather conditions and the photoperiod of Iceland. The planning of the Hekluskόgar project was initiated in 2005 with the main goal of restoring the native birch woodlands in the vicinity of Mount Hekla to increase the resilience of the land to eruptions and other natural disasters, while providing a healthier environment for the local community as well as increased land use options and community resilience. This large-scale restoration project has already some success stories after more than 10 years of operation, but maintaining enthusiasm and dedication among the diverse and multiple stakeholders, as well as working with the limited financial resources, continues to be a challenge. In several decades’ time, a successful ecosystem restoration is anticipated to provide potential future opportunities for the different stakeholders involved. ...